Estudo genético e epigenético do fibroma cemento-ossificante - Thais dos Santos Fontes Pereira (2017)
Cemento-ossifying fibroma (COF) is an odontogenic neoplasm with an uncertain pathogenesis. We performed the next generation sequencing (NGS), using the Ion AmpliSeqCancer Hotspot Panel v2, which investigate 2855 mutations in 207 amplicons of 50 genes in seven COF samples. Moreover, we performed a transcriptional analysis of 44 genes of Wnt/-catenin pathway in six COF samples and six controls of healthy jaw bones. The miRNAs expression profile was established in nine COF cases and ten control samples using the TaqMan® OpenArray® Human MicroRNA panel containing 754 validated human miRNAs. Bioinformatics tools were used to determinate the leader genes and to investigate the signaling pathways regulated by differently expressed miRNAs in COF. NGS revealed five SNV: TP53 (rs1042522), PIK3CA (rs2230461), MET (rs33917957), KIT (rs3822214) and APC (rs33974176), but no pathogenic mutation. The expression assay revealed twelve genes of Wnt/-catenin pathway differentially expressed in COF compared to healthy bone, including up-regulation of CTNNB1, TCF7 , NKD1 and WNT5A, and down-regulation of CTNNBIP1, FRZB, FZD6, RHOU, SFRP4, WNT10A, WNT3A and WNT4. This gene expression profile suggests the activation of Wnt/-catenin signaling pathway. Expression profiling revealed eleven down-regulated miRNAs (hsa-miR-95-3p, hsa-miR-141-3p, hsa-miR-205-5p, hsa-miR-223-3p, hsa-miR-31-5p, hsa-miR-944, hsa-miR-200b-3p, hsa-miR-135b-5p, hsa-miR-31-3p, hsa-miR-223-5p, hsa-miR-200c-3p) and five up-regulated (hsa-miR-181a-5p, hsa-miR-181c-5p, hsa-miR-149-5p, hsa-miR-138-5p, hsa-miR-199a-3p) in COF. The miRNAs target genes XIAP, EZH2, MET and TGFBR1 were defined as leader genes. While no oncogenic mutation was detected in the 50 cancer genes investigated by NGS, deregulation of miRNAs and key genes associated with Wnt/-catenin signaling pathway appears to be relevant to the molecular pathogenesis of COF. The genes XIAP, EZH2, MET and TGFBR are potential targets for functional analysis validation.